Electronic equipment, glass cover plate and chemically strengthened microcrystalline glass
Patent Information
- Application Number
- CN202380055856.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-22
- Filing Date
- 2023-04-18
- Publication Date
- 2025-03-07
AI Technical Summary
Existing glass covers have insufficient mechanical properties in electronic devices, making it difficult to meet the drop resistance requirements of large-size and ultra-thin designs of display screens.
Chemically strengthened glass-ceramics are used, and the glass-ceramics are processed through a high-temperature ion exchange process to form chemically strengthened glass-ceramics with excellent mechanical and optical properties, and are applied in glass covers to improve drop resistance.
Significantly improves the drop resistance of glass covers and electronic devices, can effectively withstand drops on rough surfaces, reduces the risk of self-explosion, and improves optical performance.
Smart Images

Figure CN119585220A_ABST
Abstract
Description
Electronic devices, glass cover plates, and chemically strengthened glass-ceramics
[0001] This application claims priority to the Chinese patent application filed with the State Intellectual Property Office on July 22, 2022, with application number 202210872140.2 and invention name “Electronic device, glass cover and chemically strengthened microcrystalline glass”, the entire contents of which are incorporated by reference into this application. Technical Field
[0002] The present application relates to the technical field of electronic equipment, and in particular to an electronic device, a glass cover plate, and a chemically strengthened microcrystalline glass. Background Art
[0003] With the increasing popularity of electronic devices such as smartphones and tablets, the demand for larger display screens and ultra-thin electronic devices is becoming increasingly prominent, placing higher demands on the mechanical properties of the glass cover plates used to protect the display screens. Improving the mechanical properties of glass cover plates, and thereby enhancing the drop resistance of electronic devices, is a pressing technical challenge.
[0004] Summary of the Invention
[0005] Embodiments of the present application provide an electronic device, a glass cover, and a chemically strengthened glass-ceramic, which are used to improve the drop resistance of the electronic device.
[0006] To achieve the above objectives, the embodiments of the present application adopt the following technical solutions:
[0007] In a first aspect, the present application provides an electronic device comprising a glass cover plate, the glass cover plate comprising chemically strengthened microcrystalline glass, the chemically strengthened microcrystalline glass comprising a first surface and a second surface relative to each other, the chemically strengthened microcrystalline glass having a stress curve, the stress curve being a curve drawn with the distance between any point inside the chemically strengthened microcrystalline glass and the first surface or the second surface as the horizontal coordinate and the stress intensity at the point as the vertical coordinate, the area enclosed by the straight line x=50μm, y=0 and the stress curve being greater than or equal to 36000t2-21600t+3150MPa*μm, where t is the thickness of the chemically strengthened microcrystalline glass in mm.
[0008] That is, the integral area S of the stress curve L within the range x∈[50μm, DOC] is greater than or equal to 36000t²-21600t+3150MPa*μm, i.e., S ≥ 36000t²-21600t+3150MPa*μm. Here, DOC is the depth of the compressive stress layer of the chemically strengthened glass-ceramics, which refers to the depth at which the stress intensity is zero.
[0009] Because the larger the area S enclosed by the stress curve L and the straight line y = 0 and the straight line x = 50 μm, the greater the stress intensity value within the range of a depth of 50 μm and the depth of the compressive stress layer, the better the chemically strengthened micro-ceramic's resistance to rough drops, and the rougher the surface it can withstand drops. Therefore, the electronic device in the embodiment of the present application can improve the rough drop resistance of the chemically strengthened micro-ceramic by making the area S enclosed by the stress curve L of the chemically strengthened micro-ceramic and the straight line y = 0 and the straight line x = 50 μm greater than or equal to 36000t2-21600t+3150MPa*μm, that is, the integral area S of the stress curve L of the chemically strengthened micro-ceramic in the range x∈[50 μm, DOC] greater than or equal to 36000t2-21600t+3150MPa*μm, thereby improving the drop resistance of the glass cover plate and the electronic device including the glass cover plate.
[0010] In one possible implementation of the first aspect, the compressive stress layer depth of the chemically strengthened glass-ceramics is greater than or equal to 0.18t and less than or equal to 0.25t. That is, 0.18t ≤ compressive stress layer depth ≤ 0.25t. This ensures that the chemically strengthened glass-ceramics has a deeper compressive stress layer depth, allowing the compressive stress layer to form deeper in the chemically strengthened glass-ceramics. This helps improve the chemically strengthened glass-ceramics' resistance to puncture by hard objects, preventing electronic devices from breaking when dropped onto rough surfaces and colliding with protrusions on the surface.
[0011] In one possible implementation of the first aspect, the chemically strengthened glass-ceramics has a central tensile stress greater than or equal to 70 MPa, and after the chemically strengthened glass-ceramics is crushed under compression by a 10 mm diameter round-headed metal pressure rod, the average length of the longest side of the fragments is greater than or equal to 5 mm. The chemically strengthened glass-ceramics in the embodiments of the present application can ensure appropriate internal tension in the chemically strengthened glass-ceramics when the central tensile stress CT is greater than or equal to 70 MPa, thereby avoiding the risk of spontaneous explosion, providing high safety performance, and strong resistance to drops on rough surfaces.
[0012] In one possible implementation of the first aspect, the chemically strengthened glass-ceramics has a central tensile stress greater than or equal to 90 MPa, and after the chemically strengthened glass-ceramics is crushed under compression by a 10 mm diameter round-headed metal pressure rod, the average length of the longest side of the fragments is greater than or equal to 5 mm. The chemically strengthened glass-ceramics in the embodiments of the present application can ensure appropriate internal tension in the chemically strengthened glass-ceramics when the central tensile stress CT is greater than or equal to 90 MPa, thereby avoiding the risk of spontaneous explosion, providing high safety performance, and strong resistance to drops on rough surfaces.
[0013] In one possible implementation of the first aspect, the chemically strengthened glass-ceramics has a central tensile stress greater than or equal to 100 MPa, and after the chemically strengthened glass-ceramics are crushed under compression by a 10 mm diameter round-headed metal pressure rod, the average length of the longest side of the fragments is greater than or equal to 5 mm. The chemically strengthened glass-ceramics in the embodiments of the present application can ensure appropriate internal tension in the chemically strengthened glass-ceramics when the central tensile stress CT is greater than or equal to 100 MPa, thereby avoiding the risk of spontaneous explosion, providing high safety performance, and strong resistance to drops on rough surfaces.
[0014] In a possible implementation of the first aspect, the glass-ceramics used to form the chemically strengthened glass-ceramics includes a primary crystalline phase and a secondary crystalline phase, the primary crystalline phase being the crystalline phase with the highest content in the glass-ceramics, the remaining crystalline phases in the glass-ceramics other than the primary crystalline phase being the secondary crystalline phases, and the ratio of the mass fraction of the primary crystalline phase to the mass fraction of the secondary crystalline phase is greater than or equal to 5. Exemplarily, the ratio of the mass fraction of the primary crystalline phase to the mass fraction of the secondary crystalline phase is equal to 5, 6, 7, 8, 9, 10, 11, 12, 13, or 14.
[0015] In this way, by controlling the ratio of the mass fraction of the main crystalline phase to the mass fraction of the secondary crystalline phase to be greater than or equal to 5, the purity of the main crystalline phase can be improved and the number of scatterings between different crystalline phases can be reduced, thereby improving the transmittance of the microcrystalline glass, reducing the haze of the microcrystalline glass, and improving the optical properties of the microcrystalline glass, which is beneficial to improving the optical properties of the chemically strengthened microcrystalline glass.
[0016] In one possible implementation of the first aspect, the mass fraction of the secondary crystalline phase is less than or equal to 10%. For example, the mass fraction of the secondary crystalline phase can be 10%, 9.5%, 9%, 8.5%, 8%, 7.5%, 7%, 6.5%, 6%, 5.5%, 5%, 4.5%, 4%, 3.5%, 3%, 2.5%, 2%, 1.5%, 1%, etc. This can further ensure the purity of the primary crystalline phase and improve the optical properties of the glass-ceramics and chemically strengthened glass-ceramics.
[0017] In a possible implementation of the first aspect, the main crystalline phase is lithium disilicate. On the one hand, inside the glass-ceramics, the lithium disilicate crystalline phase is an irregular and non-oriented microstructure with good mechanical properties. It can improve the hardness and Young's modulus of the glass-ceramics, and thus prevent the further expansion of microcracks on the surface or inside the glass-ceramics or make the microcracks bend and not easy to spread, thereby greatly improving the strength and mechanical properties of the glass-ceramics. In this way, the lithium disilicate crystalline phase can provide the glass-ceramics with higher mechanical strength and fracture toughness, and can reduce the sensitivity of the glass-ceramics to lithium ions, improve the acid and alkali cleaning resistance of the glass-ceramics, reduce the processing difficulty of the glass-ceramics in the subsequent chemical strengthening process, and enable the glass-ceramics to undergo ion exchange to obtain additional mechanical strength, thereby improving the mechanical strength of the chemically strengthened glass-ceramics. On the other hand, the refractive index of the lithium disilicate crystal phase is close to that of glass, which can reduce the number of refractions of the microcrystalline glass, increase the transmittance of the microcrystalline glass, reduce the haze of the microcrystalline glass, and further improve the optical properties of the microcrystalline glass, thereby improving the optical properties of the chemically strengthened microcrystalline glass.
[0018] In a possible implementation manner of the first aspect, the secondary crystalline phase includes at least one of petalite, lithium metasilicate, zirconium salt, and phosphate crystals.
[0019] In a possible implementation manner of the first aspect, the main crystalline phase is lithium disilicate and the secondary crystalline phase includes at least one of petalite, lithium metasilicate, zirconium salt, and phosphate crystals.
[0020] In a possible implementation of the first aspect, the average particle size of the crystalline phase of the microcrystalline glass is less than or equal to 80 nm. Exemplarily, the average particle size of the crystalline phase of the microcrystalline glass is less than or equal to 60 nm. Or the average particle size of the crystalline phase of the microcrystalline glass is less than or equal to 40 nm. Or the average particle size of the crystalline phase of the microcrystalline glass is less than or equal to 30 nm. The above-mentioned average particle size of the crystalline phase of the microcrystalline glass is relatively small, which can ensure that the average transmittance of the microcrystalline glass is high and the haze is small, so that the microcrystalline glass has excellent optical properties, thereby ensuring the optical properties of the chemically strengthened microcrystalline glass.
[0021] In one possible implementation of the first aspect, the average crystalline particle size of the glass-ceramic is greater than or equal to 10 nm. Excessively small average crystalline particle size affects the drop resistance of the glass-ceramic. Thus, by controlling the average crystalline particle size of the glass-ceramic to no less than 10 nm, both the optical performance and drop resistance of the glass-ceramic can be achieved.
[0022] In a possible implementation of the first aspect, the transmittance of the glass-ceramics at a wavelength of 550 nm is not less than 90%.
[0023] In one possible implementation of the first aspect, the Young's modulus of the glass-ceramic is greater than or equal to 95 GPa. This improves the rigidity and impact resistance of the glass-ceramic, helps reduce deformation of the glass cover, and provides better protection for the screen. Furthermore, the glass-ceramic in the embodiments of the present application, based on its higher Young's modulus, has a higher compressive stress bearing value and strong glass safety characteristics, enabling it to withstand higher chemically strengthened stresses. This further enhances the drop resistance of the chemically strengthened glass-ceramic while reducing the processing difficulty of the chemically strengthened glass-ceramic.
[0024] In a possible implementation of the first aspect, the glass-ceramics may be treated by the following high-temperature ion exchange process to obtain chemically strengthened glass-ceramics:
[0025] S10: subjecting the microcrystalline glass to a first strengthening treatment in a first molten salt, wherein the first molten salt includes NaNO3, and the mass fraction of NaNO3 is greater than or equal to 30%, the time for the first strengthening treatment is 1.5h to 10h, and the temperature for the first strengthening treatment is 380℃ to 450℃.
[0026] S20: The microcrystalline glass that has undergone the first strengthening treatment is subjected to a second strengthening treatment in a second molten salt, wherein the second molten salt includes KNO3, and the mass fraction of KNO3 is greater than or equal to 80%. The time of the second strengthening treatment is 0.2h~6h, and the temperature of the second strengthening treatment is 380℃~450℃.
[0027] Thus, after the high-temperature ion exchange process, a chemically strengthened glass-ceramic can be obtained. Furthermore, since the glass-ceramic used to form the chemically strengthened glass-ceramic in the embodiments of the present application is lowly sensitive to lithium ion concentration, there is no need to strictly control the mass fraction of LiNO3 in the first molten salt and the second molten salt, resulting in high compatibility of the first molten salt and the second molten salt with LiNO3. Specifically, the mass fraction of LiNO3 in the first molten salt and the second molten salt can be greater than or equal to 0 and less than or equal to 3%. This can reduce the processing difficulty of the chemically strengthened glass-ceramic, extend the service life of the first molten salt and the second molten salt, and reduce processing costs, while obtaining a chemically strengthened glass-ceramic that meets the stress curve requirements.
[0028] In a possible implementation of the first aspect, the glass-ceramics is processed from a glass matrix, the chemical composition of the glass matrix including: SiO2, Al2O3, Li2O, Na2O, K2O, P2O5, and ZrO2, the sum of the mass fraction of SiO2 and the mass fraction of Al2O3 is greater than or equal to 65% and less than or equal to 80%, the mass fraction of Li2O is greater than or equal to 8% and less than or equal to 15%, the sum of the mass fraction of Na2O and the mass fraction of K2O is greater than 0 and less than or equal to 10%, and the sum of the mass fraction of P2O5 and the mass fraction of ZrO2 is greater than or equal to 5% and less than or equal to 15%. Based on the above formula, it is advantageous to prepare glass-ceramics having the above-mentioned main crystal phase type, main crystal phase purity, and average crystal phase particle size, so that the glass-ceramics have excellent mechanical and optical properties, and thus, on the premise of obtaining chemically strengthened glass-ceramics that meet the above-mentioned stress curve requirements, the processing difficulty and processing cost of the chemically strengthened glass-ceramics can be reduced.
[0029] In a possible implementation of the first aspect, a glass-ceramic is prepared by subjecting a glass substrate to a first heat treatment and a second heat treatment, wherein the first heat treatment is performed at a temperature of 500°C to 550°C for a treatment time of 1 hour to 8 hours, and the second heat treatment is performed at a temperature of 600°C to 900°C for a treatment time of 1 hour to 8 hours. Based on the above formula and heat treatment process, a glass-ceramic having the above-mentioned main crystalline phase type, main crystalline phase purity, and average crystalline phase particle size can be prepared, so that the glass-ceramic has excellent mechanical and optical properties. Furthermore, while obtaining a chemically strengthened glass-ceramic that meets the above-mentioned stress curve requirements, the processing difficulty and cost of the chemically strengthened glass-ceramic can be reduced.
[0030] In a possible implementation of the first aspect, before and after the microcrystalline glass is hot-bent, the average grain size change of the microcrystalline glass is less than or equal to 5%, and / or the haze is less than or equal to 0.2%, and / or the color coordinate |b| value of the microcrystalline glass after hot-bending is less than or equal to 0.6.
[0031] In one possible implementation of the first aspect, the electronic device further includes a middle frame and a display screen, wherein the display screen is disposed on one side of the middle frame, and a glass cover plate is stacked with the display screen, with the glass cover plate being located on a side of the display screen facing away from the middle frame. In this embodiment, the glass cover plate is used as a light-transmitting cover plate of the electronic device.
[0032] In a possible implementation of the first aspect, the electronic device further includes a middle frame and a display screen, wherein the display screen and the glass cover plate are respectively disposed on opposite sides of the middle frame. In this embodiment, the glass cover plate is used as a back cover of the electronic device.
[0033] In a possible implementation manner of the first aspect, the glass cover plate is a 3D glass cover plate.
[0034] In a second aspect, an embodiment of the present application provides a glass cover plate, comprising a chemically strengthened microcrystalline glass, the chemically strengthened microcrystalline glass comprising a first surface and a second surface relative to each other, the chemically strengthened microcrystalline glass having a stress curve, the stress curve being a curve drawn with the distance between any point inside the chemically strengthened microcrystalline glass and the first surface or the second surface as the horizontal coordinate and the stress intensity at the point as the vertical coordinate, the area enclosed by the straight line x=50μm, y=0 and the stress curve being greater than or equal to 36000t2-21600t+3150MPa*μm, where t is the thickness of the chemically strengthened microcrystalline glass in mm.
[0035] In a possible implementation of the second aspect, the depth of the compressive stress layer of the chemically strengthened glass-ceramics is greater than or equal to 0.18t and less than or equal to 0.25t, that is, 0.18t≤depth of the compressive stress layer≤0.25t.
[0036] In a possible implementation of the second aspect, the central tensile stress of the chemically strengthened microcrystalline glass is greater than or equal to 70 MPa, and after the chemically strengthened microcrystalline glass is broken under the squeezing of a 10 mm diameter round-headed metal pressure rod, the average size of the longest side of the fragments is greater than or equal to 5 mm.
[0037] In a possible implementation of the second aspect, the microcrystalline glass used to form chemically strengthened microcrystalline glass includes a main crystalline phase and a secondary crystalline phase, the main crystalline phase is the crystalline phase with the highest content in the microcrystalline glass, and the remaining crystalline phases in the microcrystalline glass except the main crystalline phase are secondary crystalline phases, and the ratio of the mass fraction of the main crystalline phase to the mass fraction of the secondary crystalline phase is greater than or equal to 5.
[0038] In a possible implementation manner of the second aspect, the mass fraction of the secondary crystalline phase is less than or equal to 10%.
[0039] In a possible implementation manner of the second aspect, the main crystalline phase is lithium disilicate, and / or the secondary crystalline phase includes at least one of petalite, lithium metasilicate, zirconium salt, and phosphate crystals.
[0040] In a possible implementation of the second aspect, the transmittance of the glass-ceramics at a wavelength of 550 nm is not less than 90%.
[0041] In a possible implementation of the second aspect, the Young's modulus of the glass-ceramics is greater than or equal to 95 GPa.
[0042] In a possible implementation of the second aspect, the glass-ceramics may be treated by the following high-temperature ion exchange process to obtain chemically strengthened glass-ceramics:
[0043] S10: subjecting the microcrystalline glass to a first strengthening treatment in a first molten salt, wherein the first molten salt includes NaNO3, and the mass fraction of NaNO3 is greater than or equal to 30%, the time for the first strengthening treatment is 1.5h to 10h, and the temperature for the first strengthening treatment is 380℃ to 450℃.
[0044] S20: The microcrystalline glass that has undergone the first strengthening treatment is subjected to a second strengthening treatment in a second molten salt, wherein the second molten salt includes KNO3, and the mass fraction of KNO3 is greater than or equal to 80%. The time of the second strengthening treatment is 0.2h~6h, and the temperature of the second strengthening treatment is 380℃~450℃.
[0045] In a possible implementation of the second aspect, the microcrystalline glass is processed from a glass matrix, and the glass matrix includes: SiO2, Al2O3, Li2O, Na2O, K2O, P2O5 and ZrO2, the sum of the mass fraction of SiO2 and the mass fraction of Al2O3 is greater than or equal to 65% and less than or equal to 80%, the mass fraction of Li2O is greater than or equal to 8% and less than or equal to 15%, the sum of the mass fraction of Na2O and the mass fraction of K2O is greater than 0 and less than or equal to 10%, and the sum of the mass fraction of P2O5 and the mass fraction of ZrO2 is greater than or equal to 5% and less than or equal to 15%.
[0046] In a possible implementation of the second aspect, the microcrystalline glass is prepared by subjecting a glass substrate to a first step heat treatment and a second step heat treatment, the temperature of the first step heat treatment is 500°C to 550°C, the treatment time is 1h to 8h, and the temperature of the second step heat treatment is 600°C to 900°C, and the treatment time is 1h to 8h.
[0047] In a possible implementation manner of the second aspect, the glass cover plate is a 3D glass cover plate.
[0048] In a possible implementation manner of the second aspect, the glass cover plate is used as a light-transmitting cover plate or back cover of an electronic device.
[0049] In a third aspect, the present application proposes a chemically strengthened microcrystalline glass, which includes a first surface and a second surface relative to each other. The chemically strengthened microcrystalline glass has a stress curve, which is a curve drawn with the distance between any point inside the chemically strengthened microcrystalline glass and the first surface or the second surface as the horizontal coordinate and the stress intensity at the point as the vertical coordinate. The area enclosed by the straight line x=50μm, y=0 and the stress curve is greater than or equal to 36000t2-21600t+3150MPa*μm, where t is the thickness of the chemically strengthened microcrystalline glass, in mm.
[0050] In a possible implementation of the third aspect, the central tensile stress of the chemically strengthened microcrystalline glass is greater than or equal to 70 MPa, and after the chemically strengthened microcrystalline glass is broken under the squeezing of a 10 mm diameter round-headed metal pressure rod, the average size of the longest side of the fragments is greater than or equal to 5 mm.
[0051] Among them, the technical effects brought about by any design method in the second to third aspects can refer to the technical effects brought about by different design methods in the first aspect, and will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] FIG1 is a schematic diagram of the structure of an electronic device provided in some embodiments of the present application;
[0053] FIG2 is a cross-sectional view of the electronic device shown in FIG1 taken along line AA;
[0054] FIG3 is a cross-sectional view of chemically strengthened glass-ceramics provided in some embodiments of the present application;
[0055] FIG4 is an internal stress curve of chemically strengthened glass-ceramics provided in some embodiments of the present application.
[0056] Figure numerals: 100, electronic device; 10, screen; 11, light-transmitting cover; 12, display screen; 13, chemically strengthened microcrystalline glass; 131, first surface; 132, second surface; 20, middle frame; 21, border; 22, middle plate; 30, back cover; 40, circuit board; 41, main circuit board; 42, auxiliary circuit board; 50, battery. DETAILED DESCRIPTION
[0057] In the embodiments of this application, the terms "exemplary" or "for example" are used to indicate an example, illustration, or description. Any embodiment or design described as "exemplary" or "for example" in the embodiments of this application should not be interpreted as being more preferred or advantageous over other embodiments or designs. Rather, the use of words such as "exemplary" or "for example" is intended to present the relevant concepts in a concrete manner.
[0058] In the embodiments of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood to indicate or imply relative importance or implicitly specify the number of technical features indicated. Therefore, features defined as "first" or "second" may explicitly or implicitly include one or more of the features.
[0059] In the description of the embodiments of the present application, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, at least one of a, b, or c can represent: a, b, c, ab, ac, bc, or abc, where a, b, and c can be single or multiple.
[0060] In the description of the embodiments of this application, the term "and / or" refers to and encompasses any and all possible combinations of one or more of the associated listed items. The term "and / or" describes an association relationship between associated objects, indicating that three relationships can exist. For example, A and / or B can represent: A exists alone, A and B exist simultaneously, and B exists alone. In addition, the character " / " in this application generally indicates that the associated objects are in an "or" relationship.
[0061] In the description of the embodiments of this application, it should be noted that, unless otherwise expressly specified or limited, the terms "mounted," "connected," and "connected" should be understood in a broad sense. For example, "connected" can mean detachably connected or non-detachably connected; directly connected or indirectly connected through an intermediary. "Fixedly connected" means connected so that the relative positional relationship remains unchanged after connection.
[0062] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, the terms "installed", "connected" and "connected" should be understood in a broad sense. For example, "connection" can be a detachable connection or a non-detachable connection; it can be a direct connection or an indirect connection through an intermediate medium.
[0063] In the description of the embodiments of the present application, the terms "comprises", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device comprising a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element limited by the statement "comprising a ..." does not exclude the presence of other identical elements in the process, method, article or device comprising the element. In the absence of further restrictions, an element limited by the statement "comprising a ..." does not exclude the presence of other identical elements in the process, method, article or device comprising the element.
[0064] An embodiment of the present application provides an electronic device including a glass cover plate, which can be used as a light-transmitting cover plate, back cover, or the like of the electronic device. The glass cover plate comprises chemically strengthened glass-ceramic. That is, at least a portion of the glass cover plate is processed from chemically strengthened glass-ceramic.
[0065] In order to improve the drop resistance of electronic devices, in the electronic devices provided in the embodiments of the present application, the area enclosed by the stress curve L of the chemically strengthened microcrystalline glass and the straight line x = 50 μm, y = 0 is greater than or equal to 36000t 2 -21600t+3150MPa*μm. That is, the integral area of the stress curve L of the chemically strengthened glass-ceramics in the range of x∈[50μm,DOC] is greater than or equal to 36000t 2 -21600t+3150MPa*μm, where DOC is the depth of the compressive stress layer of the chemically strengthened glass-ceramic, t is the thickness of the chemically strengthened glass-ceramic, and the unit of t is mm. Since the larger the integrated area of the stress curve L of the chemically strengthened glass-ceramic within the range of x∈[50μm, DOC], the better the chemically strengthened glass-ceramic's resistance to drops from rough surfaces, and the greater the surface roughness that the chemically strengthened glass-ceramic can withstand, the glass cover plate of the electronic device in the embodiment of the present application and the electronic device including the glass cover plate have a higher compressive stress bearing value, which significantly improves the electronic device's ability to resist drops from rough surfaces.
[0066] The electronic devices provided in the embodiments of the present application include, but are not limited to, mobile phones, tablet personal computers, laptop computers, personal digital assistants (PDAs), personal computers, notebook computers, vehicle-mounted devices, and wearable devices. The embodiments of the present application do not impose any particular restrictions on the specific form of the above-mentioned electronic devices.
[0067] Please refer to Figures 1 and 2. Figure 1 is a schematic diagram of the structure of an electronic device 100 provided in some embodiments of the present application, and Figure 2 is a cross-sectional view of the electronic device 100 shown in Figure 1 taken along line AA. In this embodiment, the electronic device 100 is a tablet phone. Specifically, the electronic device 100 includes a screen 10, a middle frame 20, a back cover 30, a circuit board 40, and a battery 50. Because the circuit board 40 and battery 50 are located inside the electronic device 100 and are not visible, they are represented by dotted lines in Figure 1.
[0068] It should be understood that Figures 1 and 2 and the following related figures only schematically illustrate some components of the electronic device 100, and the actual shape, size, position, and structure of these components are not limited by Figures 1 and 2 and the following figures. In some other embodiments, the electronic device 100 may not include the screen 10.
[0069] The screen 10 is used to display images, videos, etc. The screen 10 may include a translucent cover plate 11 and a display screen 12. The translucent cover plate 11 is stacked and fixedly connected to the display screen 12. The translucent cover plate 11 is mainly used to protect the display screen 12 and prevent dust. The translucent cover plate 11 may be a 2D cover plate, a 2.5D cover plate or a 3D cover plate. Among them, the 2D cover plate is an ordinary pure plane without any curved design. All points on the cover plate are on the same plane, and such cover plates are collectively referred to as 2D cover plates. The 2.5D cover plate is flat in the middle, but has a certain curved design on the edges. Compared with the 2D cover plate, the 2.5D cover plate has curved edges based on the flat cover plate. The 3D cover plate adopts a curved design in both the middle and edge parts of the flat cover plate. The curved surface design in the 3D cover plate can increase the visible area, better conform to the curvature of the human eye retina, and bring a better visual experience.
[0070] The display screen 12 can be a flexible display screen or a rigid display screen.
[0071] The middle frame 20 is the "support skeleton" of the electronic device 100. Referring to Figure 2 , the middle frame 20 includes a frame 21 and a middle plate 22. The middle plate 22 is fixed to the inner surface of the frame 21. For example, the middle plate 22 can be fixed to the frame 21 by welding, or the middle plate 22 and the frame 21 can be integrally molded. The screen 10 is fixedly connected to one side of the frame 21 by means of a translucent cover plate 11. For example, the translucent cover plate 11 can be fixed to the frame 21 by gluing.
[0072] The back cover 30 is fixedly connected to the side of the middle frame 20 away from the screen 10. The frame 21 is located between the back cover 30 and the transparent cover 11. The transparent cover 11, the back cover 30 and the frame 21 form an internal storage space of the electronic device 100, which accommodates the display screen 12, the circuit board 40, etc. Exemplarily, the back cover 30 can be fixedly connected to the frame 21 by gluing. The circuit board 40, the battery 50, etc. can be fixedly connected to the middle plate 22 by means of threaded connection, clamping, welding, etc. The back cover 30 can be a 2D cover, a 2.5D cover, or a 3D cover.
[0073] In some embodiments, in order to improve the appearance of the electronic device 100, one of the transparent cover plate 11 and the back cover 30 is set to a glass cover plate, or both the transparent cover plate 11 and the back cover 30 are set to glass cover plates. In addition, as users have higher and higher requirements for electronic devices 100, in order to provide users with a better user experience, more and more mobile phones, especially high-end mobile phones, adopt 3D glass cover plate designs (that is, curved cover plates). However, 3D glass cover plates are more fragile and more expensive than 2D cover plates, so there is an urgent need to design glass cover plates that are more resistant to falling.
[0074] On this basis, in order to improve the drop resistance of the electronic device 100, the glass cover in some embodiments includes chemically strengthened microcrystalline glass. Specifically, the glass cover can be made entirely of chemically strengthened microcrystalline glass, or the glass cover can be made partially of chemically strengthened microcrystalline glass.
[0075] Among them, microcrystalline glass refers to a basic glass of a specific composition with a nucleating agent (or without a nucleating agent). It is subjected to crystallization heat treatment under a certain temperature system, and a large number of tiny crystals are uniformly precipitated in the glass to form a dense multiphase complex of microcrystalline phase and glass phase.
[0076] Chemically strengthened glass-ceramics can be obtained after the glass-ceramics is treated with a high-temperature ion exchange process (also known as a chemical strengthening process). After the ion exchange, the alkali metal ions on the surface of the glass-ceramics are replaced by alkali metal ions with larger diameters to obtain chemically strengthened glass-ceramics. Exemplarily, in the high-temperature ion exchange process, the lithium ions in the glass-ceramics can be replaced by sodium ions in the molten salt (also known as the salt bath), and the sodium ions in the glass-ceramics can be replaced by potassium ions in the salt bath. This results in a volume difference being formed on the surface of the chemically strengthened glass-ceramics before and after the ion exchange. The volume difference forms a compressive stress layer of a certain depth on the surface of the chemically strengthened glass-ceramics. The compressive stress layer can eliminate or inhibit the generation and expansion of microcracks on the surface of the chemically strengthened glass-ceramics, thereby achieving the purpose of improving the mechanical properties of the chemically strengthened glass-ceramics.
[0077] In order to further improve the strength of chemically strengthened microcrystalline glass and obtain higher performance, so that chemically strengthened microcrystalline glass can have good anti-drop performance on different rough surfaces (such as marble floors, asphalt roads, etc.), please refer to Figure 3, which is a cross-sectional view of the chemically strengthened microcrystalline glass 13 provided in some embodiments of the present application. The chemically strengthened microcrystalline glass 13 in this embodiment is a 3D form. The chemically strengthened microcrystalline glass 13 has a first surface 131 and a second surface 132 relative to each other in the thickness direction. Please refer to Figure 4, which is an internal stress curve of the chemically strengthened microcrystalline glass provided in some embodiments of the present application. The stress curve L is a curve drawn with the distance from any point inside the chemically strengthened microcrystalline glass 13 to the first surface 131 or the second surface 132 as the horizontal coordinate and the stress intensity at the point as the vertical coordinate. Among them, the horizontal coordinate can also be recorded as depth, the unit is mm, and the unit of the vertical coordinate is MPa. The stress curve can be measured using a scattered light photoelastic stress meter SLP2000. Of course, the present application is not limited to this, and the stress curve can also be measured by other stress testers.
[0078] In order to ensure the drop resistance of chemically strengthened glass-ceramics, please refer to Figure 4. The area S enclosed by the stress curve L of the chemically strengthened glass-ceramics provided in some embodiments of the present application and the straight line y = 0 and the straight line x = 50 μm is greater than or equal to 36000t. 2 -21600t+3150MPa*μm. t is the total thickness of the chemically strengthened glass-ceramics, and the unit of t is mm. It should be noted that the thickness of the chemically strengthened glass-ceramics in the embodiment of the present application is the distance between the first surface and the second surface.
[0079] That is, the integral area S of the stress curve L in the range of x∈[50μm,DOC] is greater than or equal to 36000t 2 -21600t+3150MPa*μm, that is, S≥36000t 2 -21600t+3150MPa*μm. DOC is the depth of the compressive stress layer of chemically strengthened glass-ceramics, and the depth of the compressive stress layer refers to the depth where the stress intensity is zero.
[0080] Since the larger the area S enclosed by the stress curve and the straight line y=0 and the straight line x=50μm, the greater the stress intensity value within the range of the depth of 50μm and the depth of the compressive stress layer, the better the chemically strengthened microcrystalline glass's resistance to rough drops, and the rougher the surface it can withstand drops. Therefore, the electronic device in the embodiment of the present application makes the area S enclosed by the stress curve L of the chemically strengthened microcrystalline glass and the straight line y=0 and the straight line x=50μm greater than or equal to 36000t2-21600t+3150MPa*μm, that is, the integral area S of the stress curve L of the chemically strengthened microcrystalline glass within the range of x∈[50μm,DOC] is greater than or equal to 36000t 2 -21600t+3150MPa*μm can improve the rough drop resistance of chemically strengthened microcrystalline glass, thereby improving the drop resistance of the glass cover and the electronic equipment including the glass cover.
[0081] In some embodiments of the present application, the compressive stress layer depth of the chemically strengthened glass-ceramics is greater than or equal to 0.18t and less than or equal to 0.25t. In other words, 0.18t ≤ compressive stress layer depth ≤ 0.25t. This ensures that the chemically strengthened glass-ceramics has a deeper compressive stress layer depth, allowing the compressive stress layer to form deeper in the chemically strengthened glass-ceramics. This helps improve the chemically strengthened glass-ceramics' resistance to puncture from hard objects, preventing electronic devices from breaking when they fall onto rough surfaces and collide with protrusions on the rough surface.
[0082] Furthermore, the central tensile stress CT of the chemically strengthened glass-ceramics in the embodiment of the present application is greater than or equal to 70 MPa, and when the chemically strengthened glass-ceramics is squeezed to break by a 10 mm diameter round-headed metal pressure rod, the average size of the longest side of the fragments is greater than or equal to 5 mm. It should be noted that the "average size of the longest side of the fragments" described in the present application refers to the average value of the longest side size of the fragments formed when the chemically strengthened glass-ceramics is squeezed to break by a 10 mm diameter round-headed metal pressure rod. When calculating, the sizes of the longest sides of each fragment can be added together and then divided by the number of fragments. That is, the average size of the longest side of the fragments is equal to the sum of the sizes of the longest sides of each fragment divided by the number of fragments.
[0083] The central tensile stress CT refers to the absolute value of the stress intensity at a depth of half t (i.e., t / 2) in the chemically strengthened glass-ceramics. For example, in the example shown in FIG4 , the thickness of the chemically strengthened glass-ceramics is 0.62 mm. The absolute value of the stress intensity at a depth of 0.31 mm is the central tensile stress CT of the chemically strengthened glass-ceramics.
[0084] Furthermore, the central tensile stress CT of the chemically strengthened microcrystalline glass is greater than or equal to 90 MPa, and when the chemically strengthened microcrystalline glass is squeezed by a 10 mm diameter round-headed metal pressure rod until it breaks, the average size of the longest side of the fragments is greater than or equal to 5 mm.
[0085] Furthermore, the central tensile stress CT of the chemically strengthened microcrystalline glass is greater than or equal to 100 MPa, and when the chemically strengthened microcrystalline glass is squeezed by a 10 mm diameter round-headed metal pressure rod until it breaks, the average size of the longest side of the fragments is greater than or equal to 5 mm.
[0086] After the microcrystalline glass is strengthened, the compressive stress and tensile stress are in a complementary state, keeping the overall stress of the glass in balance. Increasing the compressive stress of the glass will increase the corresponding central tensile stress. The intrinsic strength of the glass depends on the material and thickness. When the central tensile stress CT of the glass is too high and reaches the intrinsic strength limit of the glass, there will be a risk of self-explosion. The chemically strengthened microcrystalline glass in the embodiment of the present application can ensure that the internal tension of the chemically strengthened microcrystalline glass is appropriate when the central tensile stress CT is greater than or equal to 70Mpa, 90Mpa, and 100Mpa, thereby avoiding the risk of self-explosion, having high safety performance and strong resistance to falling on rough ground.
[0087] In the embodiments of the present application, chemical glass-ceramics are obtained by treating glass-ceramics with a high-temperature ion exchange process (also known as a chemical strengthening process). Glass-ceramics include a primary crystalline phase and secondary crystalline phases. The primary crystalline phase is the most abundant crystalline phase in the glass-ceramics, while the secondary crystalline phases are the remaining crystalline phases.
[0088] Based on any of the above embodiments, in order to ensure the drop resistance of chemically strengthened glass-ceramics while also ensuring the optical properties of the chemically strengthened glass-ceramics and to reduce the processing difficulty of the chemically strengthened glass-ceramics, in some embodiments, the main crystalline phase is lithium disilicate (Li2Si2O5). On the one hand, within the glass-ceramics, the lithium disilicate crystalline phase has an irregular and non-oriented microstructure with excellent mechanical properties, which can increase the hardness and Young's modulus of the glass-ceramics, thereby preventing further expansion of microcracks on the surface or within the glass-ceramics or deflecting the microcracks so that they are less likely to spread, thereby significantly improving the strength and mechanical properties of the glass-ceramics.
[0089] In this way, the lithium disilicate crystalline phase can provide the glass-ceramics with higher mechanical strength and fracture toughness, reduce the glass-ceramics' sensitivity to lithium ions, improve the glass-ceramics' resistance to acid and alkali cleaning, and reduce the difficulty of processing the glass-ceramics during subsequent chemical strengthening. This allows the glass-ceramics to undergo ion exchange to gain additional mechanical strength, thereby improving the mechanical strength of the chemically strengthened glass-ceramics. Furthermore, the refractive index of the lithium disilicate crystalline phase is close to that of glass, which can reduce the number of refractions of the glass-ceramics, increase the transmittance of the glass-ceramics, and reduce the haze of the glass-ceramics, thereby further improving the optical properties of the glass-ceramics, and thus improving the optical properties of the chemically strengthened glass-ceramics.
[0090] In some embodiments, the secondary crystalline phase includes one or more of petalite, lithium metasilicate, zirconium salt, and phosphate crystals.
[0091] On the basis of any of the above embodiments, the ratio of the mass fraction of the main crystalline phase to the mass fraction of the secondary crystalline phase is greater than or equal to 5. That is, the mass fraction of the main crystalline phase is 5 times or more than the mass fraction of the secondary crystalline phase. The mass fraction of the main crystalline phase is calculated as follows: the mass fraction of the main crystalline phase is equal to the mass of the main crystalline phase divided by the mass of the microcrystalline glass. The mass fraction of the secondary crystalline phase is calculated as follows: the mass fraction of the secondary crystalline phase is equal to the mass of the secondary crystalline phase divided by the mass of the microcrystalline glass. Exemplarily, the ratio of the mass fraction of the main crystalline phase to the mass fraction of the secondary crystalline phase is equal to 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, etc.
[0092] In this way, by controlling the ratio of the mass fraction of the main crystalline phase to the mass fraction of the secondary crystalline phase to be greater than or equal to 5, the purity of the main crystalline phase can be improved and the number of scatterings between different crystalline phases can be reduced, thereby improving the transmittance of the microcrystalline glass, reducing the haze of the microcrystalline glass, and improving the optical properties of the microcrystalline glass, which is beneficial to improving the optical properties of the chemically strengthened microcrystalline glass.
[0093] To further ensure the purity of the primary crystalline phase and improve the optical properties of glass-ceramics and chemically strengthened glass-ceramics, in some embodiments, the mass fraction of the secondary crystalline phase in the glass-ceramics is less than or equal to 10%. For example, the mass fraction of the secondary crystalline phase can be 10%, 9.5%, 9%, 8.5%, 8%, 7.5%, 7%, 6.5%, 6%, 5.5%, 5%, 4.5%, 4%, 3.5%, 3%, 2.5%, 2%, 1.5%, 1%, etc.
[0094] In some embodiments, the average particle size of the crystalline phase of the microcrystalline glass (that is, the average grain size) is less than or equal to 80 nm. Exemplarily, the average particle size of the crystalline phase of the microcrystalline glass is less than or equal to 60 nm. Or the average particle size of the crystalline phase of the microcrystalline glass is less than or equal to 40 nm. Or the average particle size of the crystalline phase of the microcrystalline glass is less than or equal to 30 nm. The above-mentioned average particle size of the crystalline phase of the microcrystalline glass is relatively small, which can ensure that the average transmittance of the microcrystalline glass is high and the haze is small, so that the microcrystalline glass has excellent optical properties, thereby ensuring the optical properties of the chemically strengthened microcrystalline glass.
[0095] The average crystal phase particle size is the average of the crystal phase particle sizes, and can be measured using a scanning electron microscope (SEM) or an X-ray diffraction (XRD) spectrometer.
[0096] On this basis, the average particle size of the crystal phase of the microcrystalline glass is greater than or equal to 10nm. Exemplarily, the average particle size of the crystal phase of the microcrystalline glass is 10nm to 80nm, or 10nm to 70nm, or 10nm to 60nm, or 10nm to 30nm. If the average particle size of the crystal phase is too small, the drop resistance of the microcrystalline glass will be affected. Therefore, by controlling the average particle size of the crystal phase of the microcrystalline glass to no less than 10nm, the optical properties and drop resistance of the microcrystalline glass can be taken into account.
[0097] In the embodiments of the present application, by controlling the type of the main crystal phase in the microcrystalline glass, the purity of the main crystal phase and the average particle size of the crystal phase, the microcrystalline glass can have excellent optical properties and drop resistance, and the processing difficulty of chemically strengthened microcrystalline glass can be reduced.
[0098] Specifically, it has been measured that when the thickness is less than 1.3 mm, the transmittance of the microcrystalline glass at a wavelength of 550 nm is not less than 90%.
[0099] In some embodiments, the Young's modulus of the microcrystalline glass is greater than or equal to 95GPa. Preferably, the Young's modulus of the microcrystalline glass is greater than or equal to 100GPa. More preferably, the Young's modulus of the microcrystalline glass is greater than or equal to 110GPa. In this way, the rigidity and impact resistance of the microcrystalline glass can be improved, which is beneficial to reduce the deformation of the glass cover, so that the screen can be better protected. In addition, the microcrystalline glass in the embodiment of the present application is based on a higher Young's modulus, which enables the microcrystalline glass to have a higher compressive stress bearing value and strong glass safety characteristics, and can be used to bear higher chemical strengthening stress, thereby further improving the drop resistance of the chemically strengthened microcrystalline glass while reducing the processing difficulty of the chemically strengthened microcrystalline glass.
[0100] Specifically, the glass-ceramics in the embodiment of the present application can be processed by the following high-temperature ion exchange process (also known as a chemical strengthening process) to obtain chemically strengthened glass-ceramics:
[0101] S10: subjecting the microcrystalline glass to a first strengthening treatment in a first molten salt, wherein the first molten salt includes NaNO3, and the mass fraction of NaNO3 is greater than or equal to 30%. For example, the mass fraction of NaNO3 is 30%, 33%, 35%, 40%, 45%, 50%, 55%, 60%, etc.
[0102] In some embodiments, the first strengthening treatment is performed for 1.5 to 10 hours at a temperature of 380° C. to 450° C. For example, the first strengthening treatment is performed for 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, etc. The first strengthening treatment is performed at a temperature of 380° C., 390° C., 400° C., 410° C., 420° C., 430° C., 440° C., 450° C., etc.
[0103] S20: The microcrystalline glass that has undergone the first strengthening treatment is subjected to a second strengthening treatment in a second molten salt, wherein the second molten salt includes KNO3, and the mass fraction of KNO3 is greater than or equal to 80%. For example, the mass fraction of KNO3 is 80%, 85%, 88%, 90%, 92%, 93%, 95%, etc.
[0104] In some embodiments, the second strengthening treatment lasts for 0.2 hours to 6 hours, and the temperature of the second strengthening treatment is 380° C. to 450° C. For example, the second strengthening treatment lasts for 0.2 hours, 0.3 hours, 0.5 hours, 0.8 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, etc. The temperature of the second strengthening treatment is 380° C., 390° C., 400° C., 410° C., 420° C., 430° C., 440° C., 450° C., etc.
[0105] Thus, after the high-temperature ion exchange process, a chemically strengthened glass-ceramic can be obtained. Furthermore, since the glass-ceramic used to form the chemically strengthened glass-ceramic in the embodiments of the present application is lowly sensitive to lithium ion concentration, there is no need to strictly control the mass fraction of LiNO3 in the first molten salt and the second molten salt, resulting in high compatibility of the first molten salt and the second molten salt with LiNO3. Specifically, the mass fraction of LiNO3 in the first molten salt and the second molten salt can be greater than or equal to 0 and less than or equal to 3%. This can reduce the processing difficulty of the chemically strengthened glass-ceramic, extend the service life of the first molten salt and the second molten salt, and reduce processing costs, while obtaining a chemically strengthened glass-ceramic that meets the stress curve requirements.
[0106] It is understood that, due to the high inherent strength of glass-ceramics, in other embodiments, only the first chemical strengthening treatment may be performed on the glass-ceramics without the second chemical strengthening treatment. This simplifies the processing steps of chemically strengthened glass-ceramics, further reduces the processing difficulty of chemically strengthened glass-ceramics, and thus further reduces the processing cost of chemically strengthened glass-ceramics.
[0107] In addition, the microcrystalline glass having the above-mentioned main crystal phase type and main crystal phase purity also has excellent hot bending performance and good processing performance of curved glass cover plates (also known as 3D glass cover plates), and is suitable for processing 3D glass cover plates.
[0108] Specifically, the microcrystalline glass in the embodiment of the present application is subjected to high-temperature hot bending at 670°C to 780°C. The average particle size change of the crystalline phase of the microcrystalline glass before and after hot bending is less than or equal to 5nm, and the mass fraction change of crystallinity is less than or equal to 5%. After hot bending, the color coordinate |b| value of the microcrystalline glass is less than or equal to 0.6, and the haze is less than or equal to 0.2%. The hot bending process has little effect on the crystalline phase in the microcrystalline glass, and the crystal phase size is stable and controllable, and the optical properties are stable and controllable. There is no need for additional compensation processing due to excessive changes in crystal phase size and / or excessive changes in optical properties.
[0109] Furthermore, the above-mentioned glass-ceramics also has good acid and alkali resistance. Specifically, the weight loss of the glass-ceramics in a 5% HCl solution at 95°C for 24 hours is no more than 0.2 mg / cm 2 The weight loss of the glass-ceramics in a 5% NaOH solution at 95°C for 6 hours is no more than 0.2 mg / cm 2 .
[0110] Excellent acid and alkali resistance ensures that this glass-ceramic meets the cleaning requirements of the 3D manufacturing process: using a cleaning solvent with a pH of 12-14, the cleaning time is ≤2 hours in an ultrasonic or flatbed cleaning machine; the change in the color coordinate |b| value of the glass-ceramic before and after cleaning is ≤0.2; after cleaning, an anti-fingerprint coating can be directly evaporated or sprayed on the surface of the glass-ceramic, and the wear resistance of this fingerprint layer meets the requirement that after 2500 rubber rubs, the water drop angle is greater than 100°. Thus, compared to the process of processing 3D glass cover plates using two strong glass, the embodiment of the present application uses the above-mentioned glass-ceramic to process 3D glass cover plates without adding new steps, the processing method is simple, and it helps to reduce processing costs.
[0111] In some embodiments, the processing steps for processing a 3D glass cover plate using the glass-ceramic are the same as those for processing a 3D glass cover plate using a second-strength glass. Specifically, the processing steps for processing a 3D glass cover plate using the glass-ceramic are: CNC → cleaning → 3D hot bending → polishing → cleaning → chemical strengthening → cleaning → printing ink → cleaning → evaporation or spraying of an anti-fingerprint layer.
[0112] In order to form glass-ceramics having the above-mentioned main crystalline phase type and main crystalline phase purity, the chemical composition of the glass matrix used to form the glass-ceramics includes SiO2, Al2O3, Li2O, Na2O, K2O, P2O5, and ZrO2. Among them, the sum of the mass fraction of SiO2 and the mass fraction of Al2O3 is greater than or equal to 65% and less than or equal to 80%, the mass fraction of Li2O is greater than or equal to 8% and less than or equal to 15%, the sum of the mass fraction of Na2O and the mass fraction of K2O is greater than 0 and less than or equal to 10%, and the sum of the mass fraction of P2O5 and the mass fraction of ZrO2 is greater than or equal to 5% and less than or equal to 15%. The mass fraction of each component in the glass matrix is calculated as follows: the mass of each component divided by the total mass of the glass matrix.
[0113] For example, in some embodiments, the sum of the mass fraction of SiO2 and the mass fraction of Al2O3 is 65%, 68%, 70%, 72%, 75%, 78%, or 80%. The mass fraction of Li2O is 8%, 9%, 10%, 11%, 12%, 12%, 14%, or 15%. The sum of the mass fraction of Na2O and the mass fraction of KO is 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%. The sum of the mass fraction of P2O5 and the mass fraction of ZrO2 is 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or 15%.
[0114] SiO2 is a component that forms the glass skeleton. As the main component of the glass network structure, it gives base glass and glass-ceramics excellent chemical stability, mechanical properties, and forming properties. During the glass crystallization process, it provides a source of SiO2 for the formation of the crystalline phase.
[0115] Al2O3 also stabilizes the glass network structure and provides improved mechanical properties and chemical durability. Because Al2O3 is larger than silicon-oxygen tetrahedrons, adding Al2O3 creates larger gaps in the glass structure, facilitating ion exchange and enhancing chemical strengthening, thereby improving the mechanical properties of the glass.
[0116] Li2O is a network-external oxide that helps reduce the viscosity of glass, promotes glass melting and clarification, and facilitates the formation of lithium disilicate crystals during the crystallization process. In addition to forming lithium silicate crystals to enhance the strength of the glass itself, Li2O can also exchange with Na during the chemical strengthening process, forming deep compressive stress. This helps introduce compressive stress into the Na / Li exchange layer, which helps improve the glass's resistance to puncture from hard objects.
[0117] Na2O and K2O can significantly reduce the viscosity of the base glass, promote the melting and clarification of the base glass, and at the same time reduce the glass crystallization temperature, so that the crystallized glass can be strengthened with K ions in the potassium nitrate molten salt, which is beneficial to enhance the chemical strengthening ability of the base glass and micro-ceramic glass.
[0118] P2O5 and ZrO2 act as nucleating agents. P2O5 promotes crystal formation, increases the crystallinity of glass-ceramics, and enhances their hardness and strength. ZrO2 increases the glass network structure, facilitating chemical strengthening of glass-ceramics, increasing the depth of the ion exchange layer in glass-ceramics products, and improving the drop ball test height of glass-ceramics. The combination of ZrO2 and P2O5 refines the crystal grains and reduces the haze of glass-ceramics and their products.
[0119] Specifically, the glass substrate can be produced by a melt casting method. After heat treatment, the glass substrate can be obtained into glass-ceramics. In some embodiments, the glass substrate is heat treated in two steps to obtain glass-ceramics having the above-mentioned main crystalline phase type and main crystalline phase purity:
[0120] The temperature of the first heat treatment is 500° C. to 550° C., and the treatment time is 1 hour to 8 hours. In some embodiments, the temperature of the first heat treatment is 500° C., 510° C., 520° C., 530° C., 540° C., 540° C., etc., and the treatment time is 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, etc.
[0121] The temperature of the second heat treatment is 600° C. to 900° C., and the treatment time is 1 hour to 8 hours. In some embodiments, the temperature of the second heat treatment is 600° C., 640° C., 650° C., 700° C., 750° C., 800° C., 850° C., 900° C., etc., and the treatment time is 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, etc.
[0122] Based on the above formula and heat treatment process, microcrystalline glass having the above main crystal phase type, main crystal phase purity and average particle size of the crystal phase can be prepared, so that the microcrystalline glass has excellent mechanical and optical properties, and thus, on the premise of obtaining chemically strengthened microcrystalline glass that meets the above stress curve requirements, the processing difficulty and processing cost of chemically strengthened microcrystalline glass can be reduced.
[0123] The following describes in detail a method for preparing a 3D glass cover plate including the chemically strengthened glass-ceramics described above in conjunction with specific embodiments.
[0124] Example 1
[0125] The preparation method of the 3D glass cover plate includes:
[0126] (1) A glass matrix was prepared by a melt casting method, wherein the glass matrix comprises: the sum of the mass fraction of SiO2 and the mass fraction of Al2O3 is 65%; the mass fraction of Li2O is 1%; the sum of the mass fraction of Na2O and the mass fraction of K2O is 10%; and the sum of the mass fraction of P2O5 and the mass fraction of ZrO2 is 10%;
[0127] (2) The prepared glass substrate was subjected to a two-step heat treatment to obtain glass-ceramics: the first step was heat treated at a temperature of 540°C for 2 h, and the second step was heat treated at a temperature of 750°C to 900°C for 5 h. It was measured that the main crystalline phase of the glass-ceramics was lithium disilicate, the ratio of the mass fraction of the main crystalline phase to the mass fraction of the secondary crystalline phase was 15, and the average particle size of the crystalline phase was 35 nm.
[0128] (3) The prepared glass-ceramics are cut / ground / polished into glass sheets, and then hot-bent into 3D shapes using a 3D graphite mold, wherein the maximum hot-bending temperature is 650°C, the hot-bending compressive stress is 0.9 MPa, and the single-station hot-bending time is 30 seconds; before and after the hot-bending, the increase in the mass fraction of the crystallinity of the glass-ceramics is no more than 5%;
[0129] (4) polishing the concave and convex surfaces of the 3D glass-ceramics obtained by the heat bending process using a 3D polishing brush;
[0130] (5) chemically strengthening the polished 3D glass-ceramics to obtain chemically strengthened glass-ceramics: the molten salt used for the chemical strengthening treatment includes NaNO3, KNO3 and LiNO3, wherein the mass fraction of NaNO3 is 30%, the mass fraction of KNO3 is 67%, the mass fraction of LiNO3 is 3%, the strengthening temperature is 380°C, and the strengthening time is 10 hours;
[0131] (6) The chemically strengthened microcrystalline glass is sequentially cleaned, printed with ink, cleaned, and evaporated with an anti-fingerprint coating to obtain a 3D glass cover.
[0132] The color difference |b| value of the chemically strengthened glass-ceramic changed by 0.12 before and after cleaning. After 2500 eraser rubs, the water drop angle of the finished product was 108°, meeting application requirements. Other properties of the 3D glass cover are shown in Table 1.
[0133] Example 2
[0134] The preparation method of the 3D glass cover plate includes:
[0135] (1) A glass matrix was prepared by a melt casting method. The glass matrix composition included: the sum of the mass fraction of SiO2 and the mass fraction of Al2O3 was 80%; the mass fraction of Li2O was 14%; the sum of the mass fraction of Na2O and the mass fraction of K2O was 1%; and the sum of the mass fraction of P2O5 and the mass fraction of ZrO2 was 5%;
[0136] (2) The prepared glass substrate was subjected to a two-step heat treatment to obtain glass-ceramics: the first step was performed at a temperature of 500°C for 4 hours, and the second step was performed at a temperature of 640°C for 5 hours. It was found that the main crystalline phase of the glass-ceramics was lithium disilicate, the ratio of the mass fraction of the main crystalline phase to the mass fraction of the secondary crystalline phase was 12, and the average particle size of the crystalline phase was 53 nm.
[0137] (3) The prepared glass-ceramics are cut / ground / polished into glass sheets, and then hot-bent into 3D shapes using a 3D graphite mold, wherein the maximum hot bending temperature is 720°C, the hot bending compressive stress is 0.5 MPa, and the single-station hot bending time is 90 seconds; before and after the hot bending, the increase in the mass fraction of the crystallinity of the glass-ceramics is no more than 3%;
[0138] (4) polishing the concave and convex surfaces of the 3D glass-ceramics obtained by the heat bending process using a 3D polishing brush;
[0139] (5) The polished 3D glass-ceramics is subjected to a first chemical strengthening treatment: the molten salt used for the first chemical strengthening treatment is pure NaNO3, that is, the mass fraction of NaNO3 is 100%, the strengthening temperature is 450°C, and the strengthening time is 0.5h;
[0140] (6) subjecting the 3D glass-ceramics after the first chemical strengthening treatment to a second chemical strengthening treatment to obtain a chemically strengthened glass-ceramics: the molten salt used for the second chemical strengthening treatment includes KNO3, NaNO3, and LiNO3, wherein the mass fraction of KNO3 is 80%, the mass fraction of NaNO3 is 19.5%, and the mass fraction of LiNO3 is 0.5%, the strengthening temperature is 380°C, and the strengthening time is 6 hours;
[0141] (7) The prepared chemically strengthened microcrystalline glass is sequentially cleaned, printed with ink, cleaned, and evaporated with an anti-fingerprint coating to obtain a 3D glass cover.
[0142] The color difference |b||b| value of the chemically strengthened glass-ceramic changed by 0.12 before and after cleaning. After 2500 eraser rubs, the water drop angle of the finished product was 118°, meeting application requirements. Other properties of the 3D glass cover are shown in Table 1.
[0143] Example 3
[0144] The preparation method of the 3D glass cover plate includes:
[0145] (1) A glass matrix was prepared by a melt casting method. The glass matrix composition included: the sum of the mass fraction of SiO2 and the mass fraction of Al2O3 was 75%; the mass fraction of Li2O was 8%; the sum of the mass fraction of Na2O and the mass fraction of K2O was 1%; and the sum of the mass fraction of P2O5 and the mass fraction of ZrO2 was 10%;
[0146] (2) The prepared glass substrate was subjected to a two-step heat treatment to obtain glass-ceramics: the first step was heat treated at a temperature of 520°C for 6 hours, and the second step was heat treated at a temperature of 760°C for 2 hours. It was measured that the main crystalline phase of the glass-ceramics was lithium disilicate, the ratio of the mass fraction of the main crystalline phase to the mass fraction of the secondary crystalline phase was 5, and the average particle size of the crystalline phase was 80 nm.
[0147] (3) The prepared glass-ceramics are cut / ground / polished into glass sheets, and then hot-bent into 3D shapes using a 3D graphite mold, wherein the maximum hot bending temperature is 750°C, the hot bending compressive stress is 0.1 MPa, and the single-station hot bending time is 120 seconds; before and after the hot bending, the increase in the mass fraction of the crystallinity of the glass-ceramics is no more than 3%;
[0148] (4) polishing the concave and convex surfaces of the 3D glass-ceramics obtained by the heat bending process using a 3D polishing brush;
[0149] (5) The polished 3D glass-ceramics is subjected to a first chemical strengthening treatment: the molten salt used for the first chemical treatment includes NaNO3 and KNO3, the mass fraction of NaNO3 is 80%, the strengthening temperature is 430°C, and the strengthening time is 2h;
[0150] (6) subjecting the 3D glass-ceramics after the first chemical strengthening treatment to a second chemical strengthening treatment to obtain a chemically strengthened glass-ceramics: the molten salt used for the second chemical strengthening treatment includes KNO3 and NaNO3, wherein the mass fraction of KNO3 is 95%, the mass fraction of NaNO3 is 5%, the strengthening temperature is 450°C, and the strengthening time is 0.2h;
[0151] (7) The prepared chemically strengthened microcrystalline glass is sequentially cleaned, printed with ink, cleaned, and evaporated with an anti-fingerprint coating to obtain a 3D glass cover.
[0152] The chemically strengthened glass-ceramic exhibited a change in its |b| value of 0.07 before and after cleaning. After 2500 eraser rubs, the finished product maintained a water drop angle of 106°, meeting application requirements. Other properties of the 3D glass cover are shown in Table 1.
[0153] Comparative Example 1
[0154] The preparation method of the 3D glass cover plate includes:
[0155] (1) A glass matrix was prepared by a melt casting method. The glass matrix composition included: the sum of the mass fraction of SiO2 and the mass fraction of Al2O3 was 75%; the mass fraction of Li2O was 8%; the sum of the mass fraction of Na2O and the mass fraction of K2O was 1%; and the sum of the mass fraction of P2O5 and the mass fraction of ZrO2 was 10%;
[0156] (2) The prepared glass substrate was subjected to a two-step heat treatment to obtain glass-ceramics: the first step was heat treated at a temperature of 540°C for 2 h, and the second step was heat treated at a temperature of 750°C to 900°C for 5 h. It was measured that the main crystalline phase of the glass-ceramics was lithium disilicate, the ratio of the mass fraction of the main crystalline phase to the mass fraction of the secondary crystalline phase was 15, and the average particle size of the crystalline phase was 35 nm.
[0157] (3) The prepared glass-ceramics are cut / ground / polished into glass sheets, and then hot-bent into 3D shapes using a 3D graphite mold, wherein the maximum hot-bending temperature is 650°C, the hot-bending compressive stress is 0.9 MPa, and the single-station hot-bending time is 30 seconds; before and after the hot-bending, the increase in the mass fraction of the crystallinity of the glass-ceramics is no more than 5%;
[0158] (4) polishing the concave and convex surfaces of the 3D glass-ceramics obtained by the heat bending process using a 3D polishing brush;
[0159] (5) chemically strengthening the polished 3D glass-ceramics to obtain chemically strengthened glass-ceramics: the molten salt used for the chemical treatment includes NaNO3, KNO3 and LiNO3, wherein the mass fraction of NaNO3 is 30%, the mass fraction of KNO3 is 67%, and the mass fraction of LiNO3 is 3%, the strengthening temperature is 370°C, and the strengthening time is 5 hours;
[0160] (6) The chemically strengthened microcrystalline glass is sequentially cleaned, printed with ink, cleaned, and evaporated with an anti-fingerprint coating to obtain a 3D glass cover.
[0161] The color difference |b| value of the chemically strengthened glass-ceramic changed by 0.12 before and after cleaning. After 2500 eraser rubs, the finished product had a water drop angle of 109°, meeting application requirements. Other properties of the 3D glass cover are shown in Table 1.
[0162] Comparative Example 2
[0163] The preparation method of the 3D glass cover plate includes:
[0164] (1) A glass matrix was prepared by a melt casting method. The glass matrix had the following components: the sum of the mass fraction of SiO2 and the mass fraction of Al2O3 was 49%; the mass fraction of Li2O was 17%; the sum of the mass fraction of Na2O and the mass fraction of K2O was 4%; and the sum of the mass fraction of P2O5 and the mass fraction of ZrO2 was 10%;
[0165] (2) The prepared glass substrate was subjected to a two-step heat treatment to obtain glass-ceramics: the first step was heat treated at a temperature of 490°C for 4 hours, and the second step was heat treated at a temperature of 640°C for 4 hours. It was measured that the main crystalline phase of the glass-ceramics was lithium disilicate, the ratio of the mass fraction of the main crystalline phase to the mass fraction of the secondary crystalline phase was 2, and the average particle size of the crystalline phase was 32 nm.
[0166] (3) The prepared glass-ceramics are cut / ground / polished into glass sheets, and then hot-bent into 3D shapes using a 3D graphite mold, wherein the maximum hot-bending temperature is 690°C, the hot-bending compressive stress is 0.4 MPa, and the single-station hot-bending time is 30 seconds;
[0167] (4) polishing the concave and convex surfaces of the 3D glass-ceramics obtained by the heat bending process using a 3D polishing brush;
[0168] (5) chemically strengthening the polished 3D glass-ceramics to obtain chemically strengthened glass-ceramics: the molten salt used for the chemical treatment includes NaNO3, KNO3 and LiNO3, wherein the mass fraction of NaNO3 is 30%, the mass fraction of KNO3 is 67%, the mass fraction of LiNO3 is 3%, the strengthening temperature is 380°C, and the strengthening time is 10 hours;
[0169] (6) The chemically strengthened microcrystalline glass is sequentially cleaned, printed with ink, cleaned, and evaporated with an anti-fingerprint coating to obtain a 3D glass cover.
[0170] The color difference |b| of the chemically strengthened glass-ceramic changed by 0.3 before and after cleaning. After 2500 eraser rubs, the water drop angle of the finished product was 68°, which did not meet application requirements. Other properties of the 3D glass cover are shown in Table 1.
[0171] Table 1 Performance of 3D glass cover plates in Examples 1-3 and Comparative Examples 1-2
[0172] As shown in Table 1, the thickness of the glass cover in Example 1 is 0.4 mm, the depth of the compressive stress layer DOC is 100 μm, the integral area S of the stress curve L in the range of x∈[50 μm, DOC] is 270 MPa*μm, and the 36000t 2-21600t+3150=270MPa*μm, satisfying S greater than or equal to 36000t 2 -21600t+3150, that is, satisfying S≥36000t 2 -21600t+3150.
[0173] The glass cover plate in this embodiment demonstrated excellent drop resistance in a drop test. Specifically, the average drop height on 180# SiC sandpaper was 1.9m, and the average drop height on 80# SiC sandpaper was 1.5m. The drop test method for the glass cover plate in this application involves attaching the glass cover plate to an electronic device sample, such as a mobile phone, and dropping it from a high position. The height at which the glass cover plate breaks is recorded, which reflects the strength of the glass cover plate.
[0174] The glass cover also has excellent optical properties, specifically: a 550nm light transmittance of 91.5%, a color difference |b| value of 0.4, and a haze of 0.08%.
[0175] The glass cover has excellent mechanical properties, specifically: Young's modulus of 106GPa, pressure layer depth DOC of 100μm, central tensile stress CT of 125MPa, and when the chemically strengthened microcrystalline glass is squeezed by a 10mm diameter round-headed metal pressure rod until it breaks, the average size of the longest side of the fragments is 9mm.
[0176] The thickness of the glass cover in Example 2 is 0.62 mm, the depth of the compressive stress layer DOC is 141 μm, the integral area S of the stress curve L in the range of x∈[50 μm, DOC] is 11004 MPa*μm, 36000t 2 -21600t+3150=3596.4MPa*μm, satisfying S greater than or equal to 36000t 2 -21600t+3150, that is, satisfying S≥36000t 2 -21600t+3150.
[0177] The glass cover plate in this embodiment showed excellent drop resistance in the drop test. Specifically, the average drop height on the 180# SiC sandpaper surface was 2.5m, and the average drop height on the 80# SiC sandpaper surface was 2.2m.
[0178] The glass cover also has excellent optical properties, specifically: 550nm light transmittance is 91.3%, color difference |b| value is 0.3, and haze is 0.1%.
[0179] The glass cover has excellent mechanical properties, specifically: Young's modulus of 95GPa, pressure layer depth DOC of 141μm, central tensile stress CT of 115MPa, and when the chemically strengthened microcrystalline glass is squeezed by a 10mm diameter round-headed metal pressure rod until it breaks, the average size of the longest side of the fragments is 5mm.
[0180] The thickness of the glass cover in Example 3 is 0.65 mm, the depth of the compressive stress layer DOC is 102 μm, the integral area S of the stress curve L in the range of x∈[50 μm, DOC] is 6350 MPa*μm, and the 36000t 2 -21600t+3150=4320MPa*μm, satisfying S greater than or equal to 36000t 2 -21600t+3150, that is, satisfying S≥36000t 2 -21600t+3150.
[0181] The glass cover plate in this embodiment showed excellent drop resistance in the drop test. Specifically, the average drop height on the 180# SiC sandpaper surface was 2.1 m, and the average drop height on the 80# SiC sandpaper surface was 1.8 m.
[0182] The glass cover also has excellent optical properties, specifically: a 550nm light transmittance of 90%, a color difference |b| value of 0.6, and a haze of 0.12%.
[0183] The glass cover has excellent mechanical properties, specifically: Young's modulus of 115GPa, pressure layer depth DOC of 102μm, central tensile stress CT of 70MPa, and when the chemically strengthened microcrystalline glass is squeezed by a 10mm diameter round-headed metal pressure rod until it breaks, the average size of the longest side of the fragments is 11mm.
[0184] The thickness of the glass cover in Comparative Example 1 is 0.4 mm, the depth of the compressive stress layer DOC is 75 μm, the integral area S of the stress curve L in the range of x∈[50 μm, DOC] is 35 MPa*μm, and the 36000t 2 -21600t+3150=270MPa*μm, does not satisfy S greater than or equal to 36000t 2 -21600t+3150, that is, does not meet S≥36000t 2 -21600t+3150.
[0185] The glass cover plate in this embodiment has unsatisfactory drop resistance in the drop test. Specifically, the average drop height on the 180# SiC sandpaper surface is only 1.4m, and the average drop height on the 80# SiC sandpaper surface is only 1m.
[0186] The thickness of the glass cover in Comparative Example 2 is 0.4 mm, the depth of the compressive stress layer DOC is 68 μm, the integral area S of the stress curve L in the range of x∈[50 μm, DOC] is 32 MPa*μm, and the 36000t 2 -21600t+3150=270MPa*μm, does not satisfy S greater than or equal to 36000t 2 -21600t+3150, that is, does not meet S≥36000t 2 -21600t+3150.
[0187] The glass cover in this embodiment has unsatisfactory drop resistance and optical properties in the drop test. Specifically, the average drop height on the 180# SiC sandpaper surface is only 1.5m, and the average drop height on the 80# SiC sandpaper surface is only 1m. The transmittance of 550nm light is 89.8%, the |b| value is 0.97, and the haze is 0.25%.
[0188] In summary, it can be seen that by making the area S enclosed by the stress curve L of the chemically strengthened microcrystalline glass and the straight line y = 0 and the straight line x = 50 μm greater than or equal to 36000t 2 -21600t+3150MPa*μm, that is, the integral area S of the stress curve L of the chemically strengthened microcrystalline glass in the range of x∈[50μm,DOC] is greater than or equal to 36000t 2 -21600t+3150MPa*μm can improve the rough drop resistance of chemically strengthened microcrystalline glass, thereby improving the drop resistance of the glass cover and the electronic equipment including the glass cover.
[0189] Please refer to Table 2, which shows the comparative results of the cleaning resistance of the glass-ceramics prepared in Example 1 and Comparative Example 2 before hot bending.
[0190] Table 2
[0191] Samples with smaller changes in |b| values before and after cleaning indicate that cleaning has less impact on surface quality and the glass is more resistant to cleaning.
[0192] As shown in Table 2, the glass-ceramics prepared in Comparative Example 2, based on the glass matrix composition and heat treatment process, had a |b| value change of 0.18 after the first wash, 0.32 after the second wash, 0.45 after the third wash, and 0.61 after the fourth wash. The |b| values of the glass-ceramics varied significantly before and after the second wash, before and after the third wash, and before and after the fourth wash. This indicates that the glass-ceramics in Comparative Example 2 have poor cleaning resistance.
[0193] In contrast, the glass-ceramics prepared in Example 1, based on the glass matrix composition and heat treatment process, had a |b| value change of 0.02 after the first wash, 0.05 after the second wash, 0.12 after the third wash, and 0.2 after the fourth wash. The changes in the |b| values of the glass-ceramics before and after the first wash, the second wash, the third wash, and the fourth wash were all small. This indicates that the glass-ceramics in Example 1 have good cleaning resistance.
[0194] In an embodiment of the present application, by setting the glass cover of the electronic device (such as a transparent cover, back cover, etc.) to the above-mentioned chemically strengthened microcrystalline glass, the compressive stress bearing value of the glass cover can be increased, which can significantly improve the electronic device's ability to resist falling on rough surfaces.
[0195] Specifically, when the chemically strengthened microcrystalline glass is used as a transparent cover or back cover of an electronic device, the electronic device exhibits excellent drop resistance in a drop test. It has been measured that the average drop height of the electronic device on 80# SiC sandpaper is not less than 1.5m, and the average drop height of the electronic device on 180# SiC sandpaper is not less than 1.9m. The drop test method for the electronic device is: the electronic device is dropped from a high place, the drop height of the glass cover is recorded, and the average drop height of the electronic device is calculated through multiple drop tests.
[0196] In this way, when the electronic device falls onto a rough surface, the glass cover of the electronic device is not easily damaged, which can effectively increase the service life of the electronic device and reduce maintenance costs.
[0197] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.
[0198] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. An electronic device, characterized in that: The invention comprises a glass cover plate, wherein the glass cover plate comprises a chemically strengthened microcrystalline glass, wherein the chemically strengthened microcrystalline glass comprises a first surface and a second surface opposite to each other, and wherein the chemically strengthened microcrystalline glass has a stress curve, wherein the stress curve is a curve drawn with the distance between any point inside the chemically strengthened microcrystalline glass and the first surface or the second surface as the horizontal coordinate and the stress intensity at the point as the vertical coordinate, and an area enclosed by a straight line x=50 μm, y=0 and the stress curve is greater than or equal to 36000t2-21600t+3150 MPa*μm, wherein t is the thickness of the chemically strengthened microcrystalline glass in mm.
2. The electronic device according to claim 1, wherein The depth of the compressive stress layer of the chemically strengthened glass-ceramics is greater than or equal to 0.18t and less than or equal to 0.25t.
3. The electronic device according to claim 1 or 2, characterized in that: The central tensile stress of the chemically strengthened glass-ceramics is greater than or equal to 70 MPa, and after the chemically strengthened glass-ceramics is crushed under the pressure of a 10 mm diameter round-head metal pressure rod, the average size of the longest side of the fragments is greater than or equal to 5 mm.
4. The electronic device according to any one of claims 1 to 3, characterized in that: The glass-ceramics used to form the chemically strengthened glass-ceramics includes a main crystalline phase and a secondary crystalline phase, and a ratio of a mass fraction of the main crystalline phase to a mass fraction of the secondary crystalline phase is greater than or equal to 5.
5. The electronic device according to claim 4, characterized in that The mass fraction of the secondary crystalline phase is less than or equal to 10%.
6. The electronic device according to claim 4 or 5, characterized in that: The main crystalline phase is lithium disilicate, and / or the secondary crystalline phase includes at least one of petalite, lithium metasilicate, zirconium salt, and phosphate crystals.
7. The electronic device according to any one of claims 4 to 6, characterized in that: The average particle size of the crystal phase of the microcrystalline glass is less than or equal to 80 nm.
8. The electronic device according to claim 7, wherein: The average particle size of the crystal phase of the microcrystalline glass is greater than or equal to 10 nm.
9. The electronic device according to any one of claims 4 to 8, characterized in that: The Young's modulus of the glass-ceramics is greater than or equal to 95 GPa.
10. The electronic device according to any one of claims 4 to 9, characterized in that: The microcrystalline glass is processed from a glass matrix, and the chemical composition of the glass matrix includes: SiO2, Al2O3, Li2O, Na2O, K2O, P2O5 and ZrO2, the sum of the mass fraction of the SiO2 and the mass fraction of the Al2O3 is greater than or equal to 65% and less than or equal to 80%, the mass fraction of the Li2O is greater than or equal to 8% and less than or equal to 15%, the sum of the mass fraction of the Na2O and the mass fraction of the K2O is greater than 0 and less than or equal to 10%, and the sum of the mass fraction of the P2O5 and the mass fraction of the ZrO2 is greater than or equal to 5% and less than or equal to 15%.
11. The electronic device according to claim 10, characterized in that The microcrystalline glass is obtained by subjecting the glass substrate to a first heat treatment and a second heat treatment, wherein the temperature of the first heat treatment is 500°C to 550°C and the treatment time is 1h to 8h, and the temperature of the second heat treatment is 600°C to 900°C and the treatment time is 1h to 8h.
12. The electronic device according to any one of claims 1 to 11, characterized in that: The glass cover plate is a 3D glass cover plate.
13. A glass cover plate, characterized in that: It includes chemically strengthened microcrystalline glass, which includes a first surface and a second surface relative to each other. The chemically strengthened microcrystalline glass has a stress curve, which is a curve drawn with the distance between any point inside the chemically strengthened microcrystalline glass and the first surface or the second surface as the horizontal coordinate and the stress intensity at the point as the vertical coordinate. The area enclosed by the straight line x=50μm, y=0 and the stress curve is greater than or equal to 36000t2-21600t+3150MPa*μm, where t is the thickness of the chemically strengthened microcrystalline glass, in mm.
14. The glass cover according to claim 13, wherein: The central tensile stress of the chemically strengthened microcrystalline glass is greater than or equal to 70 MPa, and after the chemically strengthened microcrystalline glass is crushed under the pressure of a 10 mm diameter round-headed metal pressure rod, the average size of the longest side of the fragments is greater than or equal to 5 mm.
15. The glass cover according to claim 13 or 14, characterized in that: The glass-ceramics used to form the chemically strengthened glass-ceramics includes a main crystalline phase and a secondary crystalline phase, and a ratio of a mass fraction of the main crystalline phase to a mass fraction of the secondary crystalline phase is greater than or equal to 5.
16. The glass cover according to claim 15, wherein: The mass fraction of the secondary crystalline phase is less than or equal to 10%.
17. The glass cover according to claim 15 or 16, characterized in that: The main crystalline phase is lithium disilicate, and / or the secondary crystalline phase includes at least one of petalite, lithium metasilicate, zirconium salt, and phosphate crystals.
18. A chemically strengthened glass-ceramic, characterized in that: The chemically strengthened microcrystalline glass includes a first surface and a second surface relative to each other. The chemically strengthened microcrystalline glass has a stress curve. The stress curve is a curve drawn with the distance between any point inside the chemically strengthened microcrystalline glass and the first surface or the second surface as the horizontal coordinate and the stress intensity at the point as the vertical coordinate. The area enclosed by the straight line x=50μm, y=0 and the stress curve is greater than or equal to 36000t2-21600t+3150MPa*μm, where t is the thickness of the chemically strengthened microcrystalline glass, in mm.
19. The chemically strengthened glass-ceramics according to claim 18, wherein The central tensile stress of the chemically strengthened microcrystalline glass is greater than or equal to 70 MPa, and after the chemically strengthened microcrystalline glass is crushed under the pressure of a 10 mm diameter round-headed metal pressure rod, the average size of the longest side of the fragments is greater than or equal to 5 mm.